Mekanisme Pengangkutan Sampah di Kecamatan Pasar Muara Bungo Kabupaten Bungo - Yayuk Hariyanti; Joko Susanto; Ikhsan Alfarisi; M. Chotib; Zepa Anggraini (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This research is motivated by the large amount of garbage accumulation in TPS. The waste transportation mechanism organized by the Bungo Regency Environmental Service is made so that waste transportation is more scheduled and directed so that waste at the TPS can be transported on time. The purpose of this study was to determine the mechanism of waste transportation and the factors that hinder the mechanism of waste transportation in Pasar Muara Bungo District.The method in this study is a descriptive method with a qualitative approach. The results of this study indicate that the mechanism for transporting waste in the Pasar Muara Bungo sub-district is not in accordance with the Standards for Transporting Waste at the Bungo Regency Environmental Service, this can be seen from the scheduling and routing of the truck fleet, initial inspection and preparation of vehicles, collection of waste at the TPS by closing the bins. trucks, transporting waste from TPS to TPA, loading and unloading waste at TPA, cleaning vehicles and washing vehicles and vehicles entering the garage in an orderly manner.The inhibiting factors in the mechanism of waste transportation in Pasar Muara Bungo District are: Budgetary constraints lead to a lack of provision of facilities and infrastructure for the mechanism of waste transportation. Many people still throw garbage outside of collection hours, so there is always a buildup of garbage at the TPS. There is no location for making TPS due to the densely populated location and the area close to the riverbank.